2020
DOI: 10.1126/sciadv.aax2285
|View full text |Cite
|
Sign up to set email alerts
|

Poly(amino acids) as a potent self-adjuvanting delivery system for peptide-based nanovaccines

Abstract: To be optimally effective, peptide-based vaccines need to be administered with adjuvants. Many currently available adjuvants are toxic, not biodegradable; they invariably invoke adverse reactions, including allergic responses and excessive inflammation. A nontoxic, biodegradable, biocompatible, self-adjuvanting vaccine delivery system is urgently needed. Herein, we report a potent vaccine delivery system fulfilling the above requirements. A peptide antigen was coupled with poly-hydrophobic amino acid sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 41 publications
5
103
0
Order By: Relevance
“…Peptide-based self-assembled nanostructures are one of the major class among the emerging subunit vaccines in recent years and have been shown as capable to elicit long-lasting antibody titer, [40,41] induce CD8 + T cell responses, [42,43] enhance the antitumor immune response, [44,45] provide protection against bacterial or viral infections. [43,46,47] Interestingly, a biotin-SA interaction based, pathogen-specific, self-assembled subunit vaccine system has been generated and pre-clinically tested in less than 120 days, [48] and is currently being used as a differentiated, rapid approach to finding a COVID-19 vaccine. Thus, in newly emerging pandemic, for rapid production of an effective vaccine, subunit vaccines and peptide-based self-assembled vaccine systems are promising candidates.…”
Section: Resultsmentioning
confidence: 99%
“…Peptide-based self-assembled nanostructures are one of the major class among the emerging subunit vaccines in recent years and have been shown as capable to elicit long-lasting antibody titer, [40,41] induce CD8 + T cell responses, [42,43] enhance the antitumor immune response, [44,45] provide protection against bacterial or viral infections. [43,46,47] Interestingly, a biotin-SA interaction based, pathogen-specific, self-assembled subunit vaccine system has been generated and pre-clinically tested in less than 120 days, [48] and is currently being used as a differentiated, rapid approach to finding a COVID-19 vaccine. Thus, in newly emerging pandemic, for rapid production of an effective vaccine, subunit vaccines and peptide-based self-assembled vaccine systems are promising candidates.…”
Section: Resultsmentioning
confidence: 99%
“…Polyleucine (L15), when conjugated to B-cell epitope, self-assembled into nanoparticles. These particles induced the production of high antibody titers and protected model animals against GAS [ 306 ] and hookworm [ 307 ] infections. Polyglutamic and aspartic acids (E10 and D10) formed self-adjuvanting polyelectrolyte-based complexes when mixed with peptide antigen and trimethyl chitosan (TMC), while a simple mixture of antigen with TMC did not induce strong immune responses [ 308 , 309 , 310 ].…”
Section: Peptide-based Therapiesmentioning
confidence: 99%
“…as required by changing the type and number of incorporated HAAs. While we recently demonstrated that the pHAA system can self-assemble into chain-like nanoparticle aggregates and serve as an injectable vaccine against GAS, 23 the ability of such a system to deliver antigens orally has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%